Punishing immigrants : policy, politics, and injustice - Kubrin, Charis Elizabeth; Zatz, Marjorie Sue, 1955-; Martínez, Ramiro, Jr (New perspectives in crime, deviance, and law series., 2012)
Arizona's controversial new immigration bill is just the latest of many steps in the new criminalization of immigrants. While many cite the presumed criminality of illegal aliens as an excuse for ever-harsher immigration policies, it has in fact been well-established that immigrants commit less crime, and in particular less violent crime, than the native-born and that their presence in communities is not associated with higher crime rates. Punishing Immigrants moves beyond debunking the presumed crime and immigration linkage, broadening the focus to encompass issues relevant to law and society.